Dynein, kinesin and morphological changes in optic nerve axons in a rat model with cerebrospinal fluid pressure reduction: the Beijing Intracranial and Intraocular Pressure (iCOP) study - Zhang, Zheng; Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose To examine the influence of experimentally reduced cerebrospinal fluid pressure (CSFP) as compared to elevated intraocular pressure (IOP) on axonal morphology and axonal motor proteins in retinal ganglion cells (RGCs). Methods The experimental study included 39 rats which underwent cerebrospinal fluid drainage for 6 hr, 30 rats which unilaterally underwent IOP elevation for 6 hr and 30 rats in a control group. Six hours after baseline, the animals were killed and the eyes were histologically and immunohistochemically examined. Results In experimental models in the high-IOP group and the low-CSFP group as compared to the control group, RGC axons became abnormally dilated and accumulated vesicles. Both groups as compared to the control group showed an accumulation of dynein IC (intermediate chain) at the optic nerve head and retina and a reduction in kinesin HC (heavy chain) immunoreactivity in the optic nerve fibre axons. As a corollary, Western blot analysis revealed an elevation of dynein IC protein levels in the optic nerve head and retina and a decrease in kinesin HC protein levels in the optic nerve. Conclusions Experimental models with an acute IOP rise or with an acute CSFP reduction showed similar morphologic changes in the retinal ganglion cell axons and similar immunohistochemical changes in the axonal motor proteins kinesin HC and dynein IC. It supports the hypothesis that an experimental model with an acute reduction in CSFP as well as an experimental model with an acute rise in IOP may share similarities in the process of optic nerve damage.